Pengaruh Kualitas Pelayanan Posyandu Terhadap Kepuasan Ibu Balita di Posyandu Melati Mekar Desa Margajaya Kecamatan Ngamprah - Fitriyah, Anis; Fauziya, Fizi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the influence of service quality on the satisfaction of mothers with toddlers at Posyandu Melati Mekar RW 05, Margajaya Village, Ngamprah District, West Bandung Regency. The method used is a quantitative approach with data collected through questionnaires distributed to 70 respondents using a saturated sampling technique. The results showed that the service quality at Posyandu Melati Mekar was in the